The Actor Lost in Translation? Competence vs. Presence in the Teacher-Director’s Stage Directions - ODANGIU, Filip (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
This article carries on a research approach started years ago by the author, investigating the necessary conditions for producing a creative environment, favorable for the development of the actor in the acting school. Aspects of the relation between the teacher-director with the student-actor are discussed, and a series of possible interacting means and effects of the orality between the two are revealed.